Caryocar brasiliense oil improves cardiac function by increasing Serca2a/PLB ratio despite no significant changes in cardiovascular risk factors in rats. Issue 1 (December 2017) - Oliveira, Lidiane; Moreno, Lauane; Melo, Dirceu; Costa-Pereira, Liliane; Carvalho, Mayara; Silva, Paulo; Alves, Ana; Magalhães, Flávio; Dias-Peixoto, Marco; Esteves, Elizabethe
Abstract Background Caryocar brasiliense (pequi ) oil is high in monounsaturated fat acids (MUFA), especially oleic, and in carotenoids, which have been associated with protection against cardiovascular disease. However, this food is poorly studied in this context, especially in the cardiac function. Therefore, we investigated the effects of a long-term intake ofpequi oil in systemic cardiovascular risk factors and in the ex vivo cardiac function of rats. Methods Previously, we determined fatty acids and carotenoids inpequi oil. Next, male rats were divided in C – control group feed a standard diet, and PO –pequi oil group fed the same diet addedpequi oil (+2.25 g.100 g−1 ). After 15 weeks, plasma lipids, glucose, insulin, blood pressure, heart rate, hepatic lipids were accessed and visceral fat pads were harvested. Hearts were used for the ex vivo cardiac function, histologic assays, SERCA2a and phospholanban (PLB) determinations. Results In agreement with scientific data, pequi oil had expressive amounts MUFA, especially oleic acid, and carotenoids. Hepatic triglycerides (TG) were reduced bypequi oil intake (p < 0.05). All others cardiovascular risk factors were not changed. The intrinsic heart rate was lower in PO group (p < 0.05). SERCA2a content was higher in this group (p < 0.05), without affecting PLB. Also, SERCA2a/PLB ratio increased in PO group (p < 0.05). Conclusion Pequi oil intake improved cardiac function ex vivo, despite no significant changes in systemic cardiovascular risk factors. The higher lipid offer inpequi oil diet, its composition in oleic acid and carotenoids could be related to those effects.